Sentiment Analysis of the National Capital Relocation to IKN Using TF-IDF and Logistic Regression - Ni Wayan Jeri Kusuma Dewi; Indra Pratistha; Tasya Alifah; Ni Komang Sri Wahyuni (Jurnal Krisnadana, 2026)
The relocation of the national capital from Jakarta to East Kalimantan has sparked various reactions from the public, many of which have been expressed through social media platforms such as YouTube. This study aims to analyze public responses from the perspective of sentiment and emotion toward the policy. The methodology employed involves keyword weighting using TF-IDF and Logistic Regression techniques. The data was then processed through preprocessing stages and labeled using the EmoLex Dictionary. Out of a total of 5,835 comments analyzed, the results showed that 2,180 comments (37.4%) were neutral in sentiment, followed by 2,077 comments (35.6%) with positive sentiment and 1,578 comments (27.0%) containing negative sentiment. In emotion classification, anger was the most dominant emotion, with 2,525 comments (43.3%), followed by trust with 897 comments (15.4%), anticipation with 750 comments (12.9%), and other emotions, such as disgust, neutral, sadness, fear, joy, and surprise, with smaller proportions. The results of the model performance evaluation for sentiment classification showed an accuracy of 93,9%, a precision of 94,6%, a recall of 93,0%, and an F1-score of 93,5%.